Phase structure evolution, crystal structure refinement, morphology, and electro-optical properties of heat-treated Ca0.9Ni0.1Cu2.9La0.1Ti4O12. Issue 6 (15th April 2020) - Mohammed, J.; Tchouank Tekou Carol, T.; Mukhtar, G.; Kumar, V.; Bhadu, Gopala Ram; Godara, Sachin Kumar; Maji, Pradip K.; Srivastava, A.K.
Abstract: Ni 2+ -La 3+ substituted CCTO ceramic was fabricated via sol-gel autocombustion method. After calcination at 800 ° C for 6 h, the heat-treatment temperature was varied from 800 ° C to 1000 ° C. The samples were labelled T1, T2, T3 and T4 to represent heat-treatment temperature of 800 ° C, 800/800 ° C, 800/900 ° C, and 800/1000 ° C respectively. The effect of this variation in temperature on the optical, dielectric, morphology, phase as well as crystal structure evolution was studied using various characterization tools. The XRD spectra confirm the presence of secondary phases such as CaTiO3, CuO, and anatase phase of TiO2 in all the samples except the sample with T4 . However, Raman spectroscopy shows that the sample with T4 contains some amount of these secondary phases; this contradiction arises because of the better sensitivity of Raman spectroscopy as compared to XRD. The morphology of the prepared Ni 2+ -La 3+ substituted CCTO ceramic tend to evolve with temperature as observed in FESEM micrographs, the known cubic shape of CCTO ceramic evolves with increase in temperature and becomes dominant in the sample with T4 . The observed inter planar spacing in the HRTEM support the values observed from XRD analysis whereas the SAED pattern indicate that the Ni 2+ -La 3+ substituted CCTO ceramic is polycrystalline in nature. The plot of band gap against changes in heat-treatment temperature shows a decreasing behaviour with increase in heat-treatment temperature which could be ascribed to changes in the local atomic lattice of the Ni 2+ -La 3+ substituted CCTO ceramic. The dielectric properties were explained according to internal barrier layer capacitance (IBLC) model. Dielectric analysis shows that the sample with T4 exhibits the highest values of dielectric constant (40400) at low frequency which we assumed to be a consequence of space charge polarization.